Evolution of physiological, anthropometric and technical parametres in top-level kayakers during training macrocycle - Garcia, J.; Carrasco, L.; Sanudo, B.; de Hoyo, M.; Martinez, I. C. (Archivos de medicina del deporte, 2008)
The aim of this study was to analyze the evolution of technical, physiological and anthropometric parameters during a macrocycle training period in a group of top-level kayakers. Ten male top-level kayak paddlers (all members of Spanish Kayaking National Team) participated in this investigation. The macrocyle (contemporary design) was divided in two phases or mesocycles: accumulation (5 weeks) and transformation (5 weeks). Volume training was assessed in all training sessions attending to three intensity ranges. Three testing sessions was developed during the period studied: at the beginning (week 1) of the accumulation mesocycle (T1); at the fi rst week of the transformation mesocycle (T2: week 6) and at the end of this period (T3: week 10). In each testing session an anthropometric study was made following the ISAK protocol; also, kayakers carried out a maximal graded exercise test on specifi c ergometer (Dansprint®) assessing physiological (heart rate; peak blood lactate concentration) and technical (stroke frequency) parameters. Despite training developed during 10 weeks no changes were observed in heart rate, peak blood lactate concentration and stroke frequency obtained from ergometric tests. However, anthropometric and body composition measures showed changes between T1, T2 and T3. Body mass increased between T1 and T2 (p<0.01), decreasing between T2 and T3 (p<0.01); body fat percentage and sum of six skindfolds decreased between T1 and T2 (p<0.05) and between T2 and T3 (p<0.01; p<0.05, respectively). Muscular mass increased between T1 and T2 and between T1 and T3 (p<0.01) but no were observed between T2 and T3. We can conclude that this training, developed under contemporary concept of periodization, failed to induce signifi cant changes in heart rate and peak blood lactate assessed in specifi c ergometry. Body composition variables such as body fat percentage showed a positive evolution during training periods.